Malaria Parasites: The Great Escape - Rénia, Laurent; Goh, Yun Shan (Frontiers in Immunology, 2016)
Parasites of the genus Plasmodium have a complex life cycle. They alternate between their final mosquito host and their intermediate hosts. The parasite can be either extra- or intracellular, depending on the stage of development. By modifying their shape, motility, and metabolic requirements, the parasite adapts to the different environments in their different hosts. The parasite has evolved to escape the multiple immune mechanisms in the host that try to block parasite development at the different stages of their development. In this article, we describe the mechanisms reported thus far that allow the Plasmodium parasite to evade innate and adaptive immune responses.